Novel Lom-dh Genes Play Potential Role in Promoting Egg Diapause of Locusta migratoria L. - Hao, Kun; Tu, Xiongbing; Ullah, Hidayat; McNeill, Mark Richard; Zhang, Zehua (Frontiers in Physiology, 2019)
Diapause hormone (DH) neuropeptides in insects are produced by two genes, pban and capa. DH contains a conserved sequence of WFGPRXa that mediates insect diapause responses. Lom-pban, Lom-capa, and five candidate DH precursor genes (Lom-dh1, Lom-dh2, Lom-dh3, Lom-dh4, Lom-dh5) of Locusta migratoria L. were subsequently cloned. We identified Lom-dh1 to Lom-dh5 as novel genes that encode five types (type I-V) of 44 tandem repeats of DH-like neuropeptides, which may promote egg diapause of L. migratoria. To test this hypothesis, we identified four types of eight new neuropeptides encoded by Lom-dh using liquid chromatography–tandem mass spectrometry from the central neuron system of L. migratoria under both short (S) (10:14 L: D) and long (L) (16:8 L: D) photoperiods. Later on, we synthesized four type I DH-like neuropeptides, LDH1, SDH1, LDH2, and SDH2, encoded by Lom-dh2/Lom-dh3 and injected them into fifth instar female locusts. Egg diapause rates were observed after female oviposition. The four DH-like neuropeptides significantly increased the incidence of egg diapause under the short photoperiod, but the response was absent under the long photoperiod. Injection of dsLom-dh into female adult of L. migratoria under the short photoperiod can inhibit egg diapause, with no response under the long photoperiod. This study identified a new gene class of pban/capa family and its functional role in regulating diapause.